2012
DOI: 10.9721/kjfst.2012.44.5.583
|View full text |Cite
|
Sign up to set email alerts
|

Storage Properties and Biogenic Amines Production of Makgeolli Brewed with Different Proportions of Rice and Wheat Flour

Abstract: Four kinds of makgeolli brewed with different proportions of rice and wheat flour were prepared to investigate the effects of the carbohydrates source on the storage properties, and to examine the chemical characteristics and BA (biogenic amine) contents in makgeolli stored over 30 days at 4, 10 and 20 o C, respectively. The chemical properties and BA contents were sustained at a consistent level for those makgeolli stored at 4 o C over 30 days. The alcohol content was significantly higher for makgeolli brewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…The effect of fermentation time on physicochemical properties in makgeolli mashes (40,41). 따라서 식품 중 BA 함량은 미생물의 증식 특히 젖산균과 같은 세균의 증식과 함께 증가하므로 식품의 품질이나 열악한 제조 과정의 지표로 사용할 것을 제안하고 있다 (23,24,42). 본 연구결과 누룩 E는 3종의 BA가 모두 검출되었을 뿐만 아니 Tyr: tyramine, Put: putrescine…”
Section: )unclassified
“…The effect of fermentation time on physicochemical properties in makgeolli mashes (40,41). 따라서 식품 중 BA 함량은 미생물의 증식 특히 젖산균과 같은 세균의 증식과 함께 증가하므로 식품의 품질이나 열악한 제조 과정의 지표로 사용할 것을 제안하고 있다 (23,24,42). 본 연구결과 누룩 E는 3종의 BA가 모두 검출되었을 뿐만 아니 Tyr: tyramine, Put: putrescine…”
Section: )unclassified
“…However, when the cold chain is destroyed during the distribution and storage process in the summer, microorganisms in raw makgeolli can rapidly proliferate and produce BAs (Kim et al, 2011). In our previous studies, in which raw makgeolli was stored at 4°C, 10°C, and 20°C, the physicochemical changes were found to be dependent on temperature; four types of makgeolli stored at 4°C showed little physicochemical changes, including BA production, during storage for 30 days (Kim et al, 2011;Kim and Han, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Our results indicated that an increase in total acid content did not always correspond to pH reduction. Notably, the decomposition of residual protein in makgeolli is assumed to increase amino acid contents via yeast autolysis, functioning as a buffer during storage (Kim and Han, 2012). Additionally, the BA produced from the makgeolli causes the pH to be recovered by consuming protons and releasing amines and carbon dioxide during the decarboxylation of the precursor amino acid, thereby increasing the survival rate of LAB under acidic stress conditions (Spano and Massa, 2006).…”
Section: Changes In Ph and Total Acid Content During Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus 속 위주의 유산균 등 다양한 발효 미생물이 다 수 함유되어 있으며, 최근 다양한 알코올 농도의 막걸리 제 품이 생산되고 있으나 일반적으로는 6-8%의 알코올 농도를 나타내는 저도주이다 (Kim & Han 2012;Ha et al 2014). 또한 막걸리에는 단백질, 당류 등의 다량 영양소 외에도 각 종 비타민과 유기산 및 생리활성 물질이 함유되어 있다 (Kim et al 2011;Min et al 2012;Kang et al 2014).…”
Section: 서 론 막걸리는 한국 전통 발효주로서 효모와 균류 그리고unclassified